An analysis of the role of tax legislation in promoting sustainability in the mining industry: a South African, Australian and United Kingdom perspective - Murahwi, Tadiwanashe Don (Rhodes University, Faculty of Commerce, Department of Accounting)
The mining industry contributes significantly to South Africa's economy, but is fraught with controversies due to its negative environmental, economic, and social impacts. Although tax measures are established to offset these negative externalities, the role of tax provisions in promoting sustainability within South Africa's mining sector remains underexplored. The goal of this study is to analyse the tax provisions aimed at promoting sustainability in the mining industry in South Africa, Australia and the United Kingdom, in order to identify tax provisions applying in Australia and the United Kingdom that could be introduced into South African tax legislation to strengthen the sustainability of the mining industry. In addressing the goal of the research, the thesis outlines the socio-economic and environmental impacts of mining in South Africa, discusses the sustainability discourse surrounding the industry, and analyses and compares tax provisions promoting sustainability in South Africa, Australia and the United Kingdom. An interpretative qualitative research methodology was applied in the study. The research highlighted the significant environmental degradation caused by mining, including air and water pollution, biodiversity loss, and land degradation, while also noting the socio-economic consequences, particularly for local communities and vulnerable groups. South African tax legislation, such as the Income Tax Act, Mineral and Petroleum Resources Royalty Act, and the Carbon Tax Act, aim to promote mine rehabilitation, fair taxation, contribution to the fiscus, and a reduction in emissions. What is evident from the analysis of tax provisions in Australia and the United Kingdom is that tax measures go beyond mine rehabilitation, and address issues such as tax transparency, energy consumption, and community investments, promoting sustainability by balancing economic growth with environmental stewardship. The study concludes that current tax interventions primarily address environmental degradation while neglecting the social impacts of mining. Optimizing tax policies to enhance sustainability requires a comprehensive, balanced approach that addresses environmental, economic, and social aspects, including adopting practices from Australia and the United Kingdom to promote tax transparency, community investment, and environmental protection.
Keywords: Mineral industries Taxation Law and legislation -- South Africa; Mineral industries Taxation Law and legislation Australia; Mineral industries Taxation Law and legislation United Kingdom; Mineral industries Sustainable methods; Abandoned mined lands reclamation; Environmental impact charges